Effects of Arbuscular Mycorrhizal Fungi on Rice Growth Under Different Flooding and Shading Regimes - Wang, Yutao; Bao, Xiaozhe; Li, Shaoshan (Frontiers in Microbiology, 2021)
Arbuscular mycorrhizal fungi (AMF) are present in paddy fields, where they suffer from periodic soil flooding and sometimes shading stress, but their interaction with rice plants in these environments is not yet fully explained. Based on two greenhouse experiments, we examined rice-growth response to AMF under different flooding and/or shading regimes to survey the regulatory effects of flooding on the mycorrhizal responses of rice plants under different light conditions. AMF had positive or neutral effects on the growth and yields of both tested rice varieties under non-flooding conditions but suppressed them under all flooding and/or shading regimes, emphasizing the high importance of flooding and shading conditions in determining the mycorrhizal effects. Further analyses indicated that flooding and shading both reduced the AMF colonization and extraradical hyphal density, implying a possible reduction of carbon investment from rice to AMF. The expression profiles of mycorrhizal P pathway marker genes (GintPT and OsPT11) suggested the P delivery from AMF to rice roots under all flooding and shading conditions. Nevertheless, flooding and shading both decreased the mycorrhizal P benefit of rice plants, as indicated by the significant decrease of mycorrhizal P responses, contributing to the negative mycorrhizal effects on rice production. The expression profiles of rice defense marker genes OsPR1 and OsPBZ1 suggested that regardless of mycorrhizal growth responses, AMF colonization triggered the basal defense response, especially under shading conditions, implying the multifaceted functions of AMF symbiosis and their effects on rice performance. In conclusion, this study found that flooding and shading both modulated the outcome of AMF symbiosis for rice plants, partially by influencing the mycorrhizal P benefit. This finding has important implications for AMF application in rice production.